Politeness Strategies in Sympathy Expressions in English with Reference to Vietnamese Equivalents / Le Thi Lan Anh; NHDKH Pham Thi Tuyet Huong - Le, Thi Lan Anh
The aim of the study is to investigate major similarities and differences in expressing sympathy in English and Vietnamese, particularly the communicative strategies used to express the sympathetic emotion. It aims at providing a better insight into cross-culture similarities and differences between the two languages and cultures to help language users avoid communication breakdown. To conduct this thesis, the writer will investigate and point out the research questions, data collection methods, data collection instruments, data collection procedures and outline the analytical frameworks. Thanks to these methods, the writer has indicated some interpretations to clarify the differences in choosing sympathy strategies in the two language speaking communities namely English and Vietnamese. Therefore, we, the Vietnamese, should be aware of choosing the right language terms to expressing our feelings or emotions. What language ranges are used depends on social identities, group to which we belong to, cultures, cultural practices, beliefs and values to which we subscribe. Furthermore, the interaction is also based on some factors like situations, the relations ship between the addresser and the addressees, the closeness of the relationship. Therefore, the study is hoped to have some significant implications for the improvement of communicative teaching and learning English language in Vietnam.